2014
DOI: 10.3390/ijms151018381
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability and Oxidative Stress: A Link between Diabetes and Cardiovascular Disease?

Abstract: Diabetes is associated with a two to three-fold increase in risk of cardiovascular disease. However, intensive glucose-lowering therapy aiming at reducing HbA1c to a near-normal level failed to suppress cardiovascular events in recent randomized controlled trials. HbA1c reflects average glucose level rather than glycemic variability. In in vivo and in vitro studies, glycemic variability has been shown to be associated with greater reactive oxygen species production and vascular damage, compared to chronic hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 137 publications
2
146
0
2
Order By: Relevance
“…In previous research (6,40,43), the results showed that oxidative stress and inflammation are two important mechanisms in glucose fluctuations that induce diabetes-associated cardiovascular damage. All of those results are observed in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research (6,40,43), the results showed that oxidative stress and inflammation are two important mechanisms in glucose fluctuations that induce diabetes-associated cardiovascular damage. All of those results are observed in patients.…”
Section: Discussionmentioning
confidence: 99%
“…CGM is a useful tool to assess glycemic variability as well as mean glucose [20]. Glycemic variability assessed by CGM has been shown to associate with oxidative stress/inflammatory markers, endothelial dysfunction and cognitive dysfunction, and proposed as one of the factors associated with CVD outcomes in patients with and without diabetes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways may be initiated due to hyperglycemia-induced OS: (1) The polyol pathway; (2) hexosamine pathway; (3) protein kinase C activation; and (4) formation of AGEs. [7][8][9] Any period of disease can be considered a period of stress, and therefore, some degree of hyperglycemia is normal during these times, and can be seen as initially protective and part of the adaptive response for survival. However, in acute and severe diseases, the resulting hyperglycemia can be much too high and require glycemic control therapy to manage.…”
Section: Resultsmentioning
confidence: 99%